The sacred era : a novel - Aramaki, Yoshio, 1933- (Parallel futures, 2017)
"The magnum opus of a Japanese master of speculative fiction, and a book that established Yoshio Aramaki as a leading representative of the genre, The Sacred Era is part post-apocalyptic world, part faux-religious tract, and part dream narrative. In a distant future ruled by a new Papal Court serving the Holy Empire of Igitur, a young student known only as K arrives at the capital to take The Sacred Examination, a text that will qualify him for metaphysical research service with the court. His performance earns him an assignment in the secret Planet Bosch Research Department; this in turn puts him on the trail of a heretic executed many years earlier, whose headless ghost is still said to haunt the Papal Court, which carries him on an interplanetary pilgrimage across the Space Taklamakan Desert to the Planet Loulan, where time stands still, and finally to the mysterious, supposedly mythical Planet Bosch, a giant, floating plant-world that once orbited Earth but has somehow wandered 1,000 light years away. K's journey to this strange world, seemingly sprung from Hieronymus Bosch's Garden of Earthly Delights, is a journey into inner and outer space, as the novel traffics in mystic and metaphysical questions only to transform them into technical and astrophysical problems, translating the substance of religious and mythic texts into the language of science fiction"--